Genome Wide Phosphoproteome Analysis of Zymomonas mobilis Under Anaerobic, Aerobic, and N2-Fixing Conditions - Tatli, Mehmet; Hebert, Alexander S.; Coon, Joshua J.; Amador-Noguez, Daniel (Frontiers in Microbiology, 2019)
Protein phosphorylation is a post-translational modification with widespread regulatory roles in both eukaryotes and prokaryotes. Using mass spectrometry, we performed a genome wide investigation of protein phosphorylation in the non-model organism and biofuel producer Zymomonas mobilis under anaerobic, aerobic, and N2-fixing conditions. Our phosphoproteome analysis revealed 125 unique phosphorylated proteins, belonging to major pathways such as glycolysis, TCA cycle, electron transport, nitrogen metabolism, and protein synthesis. Quantitative analysis revealed significant and widespread changes in protein phosphorylation across growth conditions. For example, we observed increased phosphorylation of nearly all glycolytic enzymes and a large fraction of ribosomal proteins during aerobic and N2-fixing conditions. We also observed substantial changes in the phosphorylation status of enzymes and regulatory proteins involved in nitrogen fixation and ammonia assimilation during N2-fixing conditions, including nitrogenase, the Rnf electron transport complex, the transcription factor NifA, GS-GOGAT cycle enzymes, and the PII regulatory protein. This suggested that protein phosphorylation may play an important role at regulating all aspects of nitrogen metabolism in Z. mobilis. This study provides new knowledge regarding the specific pathways and cellular processes that may potentially be regulated by protein phosphorylation in this important industrial organism and provides a useful road map for future experiments that investigate the physiological role of specific phosphorylation events in Z. mobilis.